Monocausal attribution and its relationship with reasoning biases in schizophrenia - Moritz, Steffen; Roesch-Ely, Daniela (Schizophrenia research, 2018)
Background: Aberrant attributional styles are counted to a set of circumscribed cognitive biases that are implicated in the pathogenesis of (paranoid) psychosis. However, evidence for a specific profile (e.g., an exaggerated self-serving bias, other-blaming bias) has become equivocal over the years. More recently, one-sided (monocausal) attributions have been reported in patients with psychosis. Methods: We compared a large sample of patients with diagnosed schizophrenia (n=145) to nonclinical controls (n=30) on a revised version of the Internal, Personal and Situational Attributions Questionnaire (IPSAQ-R). In this task, participants have to assign probability estimates to each of three potential causes (i.e., myself, others, circumstances) for a specific (negative or positive) event. Results: Participants with schizophrenia displayed an abolished self-serving bias and showed a significant preference for one-sided/monocausal attributions, which was neither correlated with jumping to conclusions nor overconfidence in errors. School education correlated with less monocausal attributions. We did not find any congruence between attributional styles with core delusional ideas. Conclusions: Our study corroborates earlier investigations showing that monocausal attributions may play a role in the pathogenesis of psychosis; this bias unlikely represents an epiphenomenon of established biases. Unexpectedly, attributional styles (e.g., external-blaming) did not shape delusional contents. The true prevalence of monocausal attributions in psychosis is perhaps underestimated in the study, as groups were equated on school education, which was correlated with monocausal attributions.